Chaperoning activity of the cyclophilin family prevents tau aggregation. (26th October 2022) - Hill, Shannon E.; Esquivel, Abigail R.; Ospina, Santiago Rodriguez; Rahal, Lauren M.; Dickey, Chad A.; Blair, Laura J.
Abstract: Tauopathies, such as Alzheimer's disease, are characterized by the misfolding and progressive accumulation of the microtubule associated protein tau. Chaperones, tasked with maintaining protein homeostasis, can become imbalanced with age and contribute to the progression of neurodegenerative disease. Cyclophilins are a promising pool of underinvestigated chaperones with peptidyl‐prolyl isomerase activity that may play protective roles in regulating tau aggregation. Using a Thioflavin T fluorescence‐based assay to monitor in vitro tau aggregation, all eight cyclophilins, which include PPIA to PPIH prevent tau aggregation, with PPIB, PPIC, PPID, and PPIH showing the greatest inhibition. The low thermal stability of PPID and the strong heparin binding of PPIB undermines the simplistic interpretation of reduced tau aggregation. In a cellular model of tau accumulation, all cyclophilins, except PPID and PPIH, reduce insoluble tau. PPIB, PPIC, PPIE, and PPIF also reduce soluble tau levels with PPIC exclusively protecting cells from tau seeding. Overall, this study demonstrates cyclophilins prevent tau fibril formation and many reduce cellular insoluble tau accumulation with PPIC having the greatest potential as a molecular tool to mitigate tau seeding and accumulation.